Post hoc analysis of SUSTAIN 6 and PIONEER 6 trials suggests that people with type 2 diabetes at high cardiovascular risk treated with semaglutide experience more stable kidney function compared with placebo - Steve Bain (Kidney International, 2023)
Glucagon-like peptide-1 receptor agonists reduce albuminuria and may stabilize the estimated glomerular filtration rate (eGFR) in people with type 2 diabetes (T2D). In this post hoc analysis of the SUSTAIN 6/PIONEER 6 trials encompassing 6480 participants at high cardiovascular risk (semaglutide, 3239 participants; placebo, 3241 participants), we investigated the effects of semaglutide versus placebo on eGFR decline. Pooled data by treatment were evaluated for annual eGFR change (total annual eGFR slope in ml/min per 1.73 m2) from baseline to end of treatment and time to persistent eGFR reductions of 30%, 40%, 50% and 57% or more, including subgroup analyses by baseline eGFR (30 to under 60 or 60 and over ml/min per 1.73 m2). In the overall population, the estimated treatment difference (ETD; semaglutide versus placebo) in annual eGFR slope was significant at 0.59 ml/min per 1.73 m2 (95% confidence interval 0.29; 0.89). The ETD was numerically largest in the 30 to under 60 ml/min per 1.73 m2 eGFR subgroup, 1.06 ml/min per 1.73 m2 (0.45; 1.67), but no significant interaction was observed for treatment effect by subgroup. Hazard ratios (semaglutide versus placebo) for time to persistent eGFR decline were under 1.0 for all eGFR thresholds in the overall population; and were numerically lower in the baseline eGFR 30 to under 60 ml/min per 1.73 m2 subgroup versus the overall population, although no significant interaction was observed for treatment effect by subgroup. Thus, pooled analyses of clinical trial data in patients with T2D suggest that semaglutide may reduce the rate of eGFR decline.